SPatiotemporal-ENcoded acoustic radiation force imaging of focused ultrasound - Qi, Xu; Sun, Jiayu; Zhu, Jiayu; Kong, Dechen; Roberts, Neil; Dong, Yijing; Huang, Xiaoqi; He, Qiang; Xing, Haoyang; Gong, Qiyong (Frontiers in Human Neuroscience, 2023)
Neuromodulation technology has provided novel therapeutic approaches for diseases caused by neural circuit dysfunction. Transcranial Focused Ultrasound (FU) is an emerging neuromodulation approach that combines noninvasiveness with relatively sharp focus, even in deep brain regions. It has numerous advantages such as high precision and good safety in neuromodulation, allowing for modulation of both peripheral and central nervous systems. To ensure accurate treatment targeting in FU neuromodulation, Magnetic Resonance Acoustic Radiation Force Imaging (MR-ARFI) sequence is crucial for the visualization of the focal point. Currently, the commonly used 2D Spin Echo ARFI (2D SE-ARFI) sequence suffers from the long acquisition time, while the Echo Planar Imaging ARFI (EPI-ARFI) sequence with a shorter acquisition time is vulnerable to the magnetic field inhomogeneities. To address these problems, we proposed a SPatiotemporal-ENcoded Acoustic Radiation Force Imaging sequence (i.e. SE-SPEN-ARFI, shortened to SPEN-ARFI) in this study. The displacement at the focal spot obtained was highly consistent with that of the SE-ARFI sequence. Our research shows that SPEN-ARFI allows for rapid image acquisition and has less image distortions even under great field inhomogeneities. Therefore, SPEN-ARFI sequence is a practical alternative for the treatment planning in ultrasound neuromodulation.